Monoclonal antibody to a conserved epitope on proteins encoded by Babesia bigemina and present on the surface of intact infected erythrocytes - Shompole, S.; Perryman, L.E.; Rurangirwa, F.R.; McElwain, T.F.; Jasmer, D.P.; Musoke, A.J.; Wells, C.W.; McGuire, T.C. (1995)
To define Babesia bigemina-specific antigens on the surface of infected erythrocytes, monoclonal antibodies (MAbs) were identified by live-cell immunofluorescence. As determined by live-cell immunofluorescence, two MAbs made to the Mexico strain reacted with the Mexico strain and three Kenya strains, while three MAbs made to the Kenya-Ngong strain reacted with the Kenya strains but not the Mexico strain. Binding of MAb 44.18 (made to the Mexico strain) to a strain-common epitope was confirmed by immunoelectron microscopy and by surface-specific immunoprecipitation of (35S) methionine-labeled proteins (200, 28 and 16 kDa in size), which also demonstrated that the MAb recognized an epitope on proteins encoded by B. bigemina. In immunoblots, the MAb bound to predominant antigens with sizes of 200 and 220 kDa in erythrocyte lysates infected with strains from Puerto Rico, St. Croix, Texcoco (Mexico), Kenya, and Mexico. Major antigens with sizes of antigens bound to erythrocytes infected with either the Mexico or Kenya strains as determined by live-cell immunofluorescence, allowing the conclusion that at least one conserved surface epitope was recognized. Calf precipitation, and infected erythrocytes sensitized with these antibodies were phagocytized by cultured bovine peripheral blood monocytes. These results provide a rationable for evaluating antigens identified by MAb 44.18 individually and as components of subunit vaccines.